2017
DOI: 10.1002/etc.3699
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical response of the Africanized honeybee exposed to fipronil

Abstract: Bees are recognized worldwide for their social, economic, and environmental value. In recent decades they have been seriously threatened by diseases and high levels of pesticide use. The susceptibility of bees to insecticides makes them an important terrestrial model for assessing environmental quality, and various biomarkers have been developed for such assessments. The present study aimed to evaluate the activity of the enzymes acetylcholinesterase (AChE), carboxylesterase (CaE), and glutathione-S-transferas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…CaEs are hydrolases catalyzing the reactions of aliphatic/ aromatic esters of a wide range of xenobiotics (Dauterman, 1985). CaE induction after honeybees' exposure to several pesticides has been described in several works (Badiou-Bénéteau et al 2012;Carvalho et al 2013;Hashimoto et al, 2003;Roat et al 2017). CaE enzymes are considered to have a double role; in fact, they may be both considered as phase I detoxifying enzymes and also as suicide enzymes that inactivate organophosphate and carbamate insecticides (Dary et al 1990;Gunning et al 1997;Stone et al 2002;Yu et al 1984).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…CaEs are hydrolases catalyzing the reactions of aliphatic/ aromatic esters of a wide range of xenobiotics (Dauterman, 1985). CaE induction after honeybees' exposure to several pesticides has been described in several works (Badiou-Bénéteau et al 2012;Carvalho et al 2013;Hashimoto et al, 2003;Roat et al 2017). CaE enzymes are considered to have a double role; in fact, they may be both considered as phase I detoxifying enzymes and also as suicide enzymes that inactivate organophosphate and carbamate insecticides (Dary et al 1990;Gunning et al 1997;Stone et al 2002;Yu et al 1984).…”
Section: Discussionmentioning
confidence: 98%
“…Biomarkers are also ideal tools to investigate the effects of mixtures of contaminants. However, up to now, biomarkers have been mostly evaluated in laboratory studies (Badawy et al 2015 ; Badiou et al 2008 ; Badiou-Bénéteau et al 2012 ; Boily et al 2013 ; Caliani et al 2021 ; Carvalho et al 2013 ; Roat et al 2017 ), while few authors used this approach in field studies (Badiou-Bénéteau et al 2013 ; Boily et al 2013 ; Lupi et al 2020 ; Wegener et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the partial inhibition may be indicative of a reduction in relative activity of this enzyme and, consequently, a decrease in the metabolism of these compounds, resulting in the high toxicity observed. The effects of fipronil on the relative activity of this esterase have also been observed in the Africanized honeybees (Nahar & Ohtani, 2015;Zaluski, Kadri, Alonso, Martins, & Orsi, 2015;Roat, Carvalho, Palma, & Malaspina, 2017;Kairo et al, 2017;Lunardi, Zaluski, & Orsi, 2017;Yasuda et al, 2017).…”
Section: Discussionmentioning
confidence: 77%
“…For example, Badiou et al 49 reported that deltamethrin significantly induced the activity of AChE in surviving honeybees Apis mellifera L., and they suggested the use of AChE as a biomarker of deltamethrin exposure. Roat et al 50 reported that fipronil changed the activity of CarE in newly emerged and aged Africanized honeybees, but it had no effect on the activity of AChE or GST. Xiong et al 51 reported that 24-h treatment of fipronil significantly induced the activity of P450, GST, and CarE in S. invicta workers.…”
Section: Discussionmentioning
confidence: 99%